Individual Trees Respond to 40 Years of Climate Change Through Leaf Functional Trait Acclimation - Riley P. Fortier; Rodolfo Vásquez Martínez; Rocío Del Pilar Rojas Gonzalez; Rachel Collins; Luis Valenzuela Gamarra; Abel Montagudo Mendoza; Oliver L. Phillips; Timothy R. Baker; J. Sebastián Tello; Kenneth J. Feeley (Global Change Biology, 2026)
Forests are vital for regulating climate and sustaining biodiversity, but climate change threatens their ability to do so, especially in the tropics. Our knowledge of how tropical forests and their constituent trees will respond to changes in climate is largely based on functional trait studies; however, few previous studies have investigated trait changes within individual tropical trees across decades, limiting our ability to predict the future of these forests. In this study, we leveraged historical and contemporary botanical specimens collected from the same individual trees in the southern Peruvian Amazon, measured a suite of leaf traits to test for individual‐level trait changes over nearly 40 years, and then related these changes to concurrent changes in local climate. We hypothesized that trees have acclimated their functional traits in response to increasing air temperatures and drought intensification and that this acclimation should help to maintain stable leaf temperatures through time. In accord with our hypothesis, we found significant decreases in measured leaf traits, including size and shape metrics and stomatal traits, within individuals through time. We used these measured traits to model leaf temperatures through time, which increased faster than would be expected based on changes in air temperature alone. This accelerated warming of leaves was due to decreased stomatal conductance, a potential acclimation of trees to dry season intensification and rising [CO 2 ], thus limiting leaf transpirational cooling. In other words, trees have decreased abilities to cool their leaves, and consequently they may be approaching critical thermal thresholds faster than they would in the absence of water limitation. Our study provides evidence that while individual trees are acclimating to climate change, tropical forests are undergoing increasing thermal stress and that intensifying drought may be elevating this risk.

A Review of Advances in Nutrition Research towards Commercial Aquaculture of Pompanos, Trachinotus spp. - Nicholas Romano; Juan F. Paredes; Fernando Yamamoto; Paul S. Wills; Charles R. Weirich; Kenneth L. Riley (Reviews in Aquaculture, 2026)
Among the jack family (Carangidae), pompanos, Trachinotus spp., are the most farmed globally. The top four most aquacultured species are golden pompano, T. ovatus , snubnose pompano, T. blochii , Indian pompano, T. mookalee , and Florida pompano, T. carolinus . While initial efforts to culture these species heavily relied on wild‐caught small fish of various species (commonly referred to as ‘trash fish’) for growout, pompanos can readily accept and thrive on formulated pelleted feeds. This has largely been accomplished through decades of nutritional research where marine‐based ingredients can be feasibly replaced with plant and animal‐based protein mixtures as long as essential amino acids, including taurine, and long‐chain polyunsaturated fatty acids meet their nutritional requirements. Obstacles still exist, including relatively poor feed efficiency, despite having a high digestibility of various ingredients, along with major research gaps in pompano nutrition and feed management of late juveniles to near‐market sized adults. Additionally, nutritional research on vitamin requirements as well as “functional feeds” and “finishing diets” designed for pompano is also relatively limited. After briefly describing the research history and production of the four most commonly farmed Trachinotus species, the main focus will be on discussing the feasibility of using alternatives to marine‐based ingredients, the influence of different starch sources, vitamin/mineral requirements, the success of “functional feeds” and the effectiveness of different feed management strategies in pompano aquaculture.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Balancing conflict and opportunity - spatial planning of shellfish and macroalgae culture systems in a heavily trafficked maritime port - Lisa C. Wickliffe; Jonathan A. Jossart; Seth J. Theuerkauf; Brandon M. Jensen; John B. King; Trent Henry; Paula C. Sylvia; James A. Morris; Kenneth L. Riley (Frontiers in Marine Science, 2024)
Ocean-based industries like shipping, aquaculture, and wind energy are growing at an unprecedented rate resulting in challenges related to siting and environmental management. As marine aquaculture and other ocean-based industries continue to expand, robust marine spatial planning analyses that reconcile existing ocean uses and integrate pertinent environmental and planning data are critical for identifying compatible locations. In this study, a series of geospatial analyses were used for aquaculture siting within and around a heavily trafficked and highly utilized maritime port in the San Diego Bay area of California, USA. Using a centralized geodatabase representing key aquaculture planning spatial datasets, recommendations for specific areas for aquaculture were developed based on appropriate environmental conditions for candidate shellfish and algae aquaculture species culture systems. Areas that were known constraints were first identified to determine potentially usable areas for shellfish and macroalgae (i.e., seaweed) aquaculture using an exclusion analysis, a type of multi-criteria decision analysis, to eliminate all areas without compatibility. Within the remaining usable area, we further considered shellfish and macroalgae culture system-specific factors within a ‘culture systems analysis’ to determine where different culture systems have potential for success. This analysis provides a foundation of coastal intelligence for guiding the aquaculture industry and natural resource managers towards appropriate siting decisions. This study can serve as a replicable example of aquaculture spatial planning approaches for siting sustainable aquaculture and other blue economy industries.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A global review of protected species interactions with marine aquaculture - Gretchen E. Bath; Carol A. Price; Kenneth L. Riley; James A. Morris (Reviews in Aquaculture, 2023)
As marine aquaculture expands around the world, there is increased concern for impacts to protected species. Documented cases of marine mammal, sea turtle, seabird, and shark interactions with aquaculture installations do exist but are challenging to find. This extensive review summarises the state of knowledge of protected species interactions with marine fish and shellfish aquaculture installations. Although seaweed aquaculture was beyond the scope of this review, some of the findings for shellfish and finfish aquaculture may be relevant. The potential impacts of farms including habitat exclusion, entanglement, entrapment, collisions, and behavioural modifications are the primary risks posed to protected species by marine aquaculture facilities and operations. In addition, indirect effects from habitat impacts of farm operations may be of concern in some areas as well as the cumulative impacts of multiple small or large farms in the same general vicinity. Decades of farm innovations and best management practices have been driven by industry, natural resource managers, conservation organisations, and international conservation agreements. This review is useful for informing industry planning and permitting to develop aquaculture in the open ocean. This work will help advance the science of conservation by synthesising the state of knowledge and provide managers and industry with more insight to protect the most vulnerable species.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Quantifying spatial extents of artificial versus natural reefs in the seascape - D’amy N. Steward; Avery B. Paxton; Nathan M. Bacheler; Christina M. Schobernd; Keith Mille; Jeffrey Renchen; Zach Harrison; Jordan Byrum; Robert Martore; Cameron Brinton; Kenneth L. Riley; J. Christopher Taylor; et al. (Frontiers in Marine Science, 2022)
With increasing human uses of the ocean, existing seascapes containing natural habitats, such as biogenic reefs or plant-dominated systems, are supplemented by novel, human-made habitats ranging from artificial reefs to energy extraction infrastructure and shoreline installments. Despite the mixture of natural and artificial habitats across seascapes, the distribution and extent of these two types of structured habitats are not well understood but are necessary pieces of information for ocean planning and resource management decisions. Through a case study, we quantified the amount of seafloor in the southeastern US (SEUS; 103,220 km 2 in the Atlantic Ocean; 10 – 200 m depth) covered by artificial reefs and natural reefs. We developed multiple data-driven approaches to quantify the extent of artificial reefs within state-managed artificial reef programs, and then drew from seafloor maps and published geological and predictive seafloor habitat models to develop three estimates of natural reef extent. Comparisons of the extent of natural and artificial reefs revealed that artificial reefs account for substantially less habitat (average of two estimates 3 km 2 ; <0.01% of SEUS) in the region than natural reefs (average of three estimates 2,654 km 2 ; 2.57% of SEUS) and that this pattern holds across finer regional groupings (e.g., states, depth bins). Our overall estimates suggest that artificial reef coverage is several orders of magnitude less than natural reef coverage. While expansive seafloor mapping and characterization efforts are still needed in SEUS waters, our results fill information gaps regarding the extent of artificial and natural reef habitats in the region, providing support for ecosystem-based management, and demonstrating an approach applicable to other regions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Meta-Analysis Reveals Artificial Reefs Can Be Effective Tools for Fish Community Enhancement but Are Not One-Size-Fits-All - Avery B. Paxton; Kyle W. Shertzer; Nathan M. Bacheler; G. Todd Kellison; Kenneth L. Riley; J. Christopher Taylor (Frontiers in Marine Science, 2020)

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)